A review of the surface and internal anatomy of the caudal canal in children. Issue 8 (26th March 2014) - Lees, David; Frawley, Geoff; Taghavi, Kiarash; Mirjalili, Seyed Ali; Bosenberg, Adrian
Summary The anatomy of the sacral hiatus and caudal canal is prone to significant variation, yet studies assessing this in the pediatric population remain limited. Awareness of the possible anatomical variations is critical to the safety and success of caudal epidural blocks, particularly when image guidance is not employed. This systematic review analyzes the available evidence on the clinical anatomy of the caudal canal in pediatric patients, emphasizing surface anatomy and internal anatomical variations. A literature search using three electronic databases and standard pediatric and anatomy reference texts was conducted yielding 24 primary and seven secondary English‐language sources. Appreciating that our current landmark‐guided approaches to the caudal canal are not well studied in the pediatric population is important for both clinicians and researchers.